Mathematics for economics and business - Jacques, Ian (Pearson Education, 2018)
Starting with the basics, the book is designed to allow you to progress at your own pace, with a wealth of examples, practice exercises and self-test questions to check your understanding along the way. Over 200 new questions have been added to this new edition, with answers provided, making it a fantastic resource for revision purposes.